2012
DOI: 10.9738/cc98.1
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Disk Herniation, a not Infrequent Cause of Chronic Abdominal Pain

Abstract: This study assesses the proportion of patients presenting with nonvisceral chronic abdominal pain who have thoracic disk herniation as a possible cause. We designed a descriptive transversal study of patients attending our offices between February 2009 and October 2010, with a complaint of chronic abdominal pain of suspected abdominal wall source (positive Carnett sign). Nuclear magnetic resonance (NMR) of the spinal column was performed on all patients. When the NMR showed thoracic disk herniation the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
1
20
0
1
Order By: Relevance
“…Given these premises, in two recent papers 11 , 12 , we published the results of a two-phase study in which a spinal MRI was performed on all patients attending our clinic with chronic abdominal pain and symptoms (with criteria of parietal pain, after the presence of an organic pathology had been rejected). Of these patients 63.82 % (30 of 47) were found to have one or more thoracic disc protrusions.…”
Section: Introductionmentioning
confidence: 99%
“…Given these premises, in two recent papers 11 , 12 , we published the results of a two-phase study in which a spinal MRI was performed on all patients attending our clinic with chronic abdominal pain and symptoms (with criteria of parietal pain, after the presence of an organic pathology had been rejected). Of these patients 63.82 % (30 of 47) were found to have one or more thoracic disc protrusions.…”
Section: Introductionmentioning
confidence: 99%
“…We can also suggest that thoracic intervertebral disc herniation may remain a missed diagnosis, if it is not considered within the range of preliminary diagnoses in cases with dorsalgia. [16][17][18][19][20] In conclusion, several conclusions may be made regarding the MRI findings in patients with dorsalgia. Magnetic resonance imaging is a precise imaging technique for investigating patients with complaint of dorsalgia.…”
Section: Discussionmentioning
confidence: 96%
“…One previous study pointed out that 18 out of 27 patients with chronic abdominal pain showed evidence of thoracic disc herniation in MRI as a reason for pain. Majority of these patients were previously diagnosed to have IBS [20]. MRI adds significant specificity in the diagnosis of these patients.…”
Section: Discussionmentioning
confidence: 99%